2020
DOI: 10.1002/pc.25718
|View full text |Cite
|
Sign up to set email alerts
|

Role of cobalt nanowire and graphene nanoplatelet on microwave shielding behavior of natural rubber composite in high frequency bands

Abstract: Highly flexible microwave shielding E (2-3 GHz), F (3-4 GHz), I (8-12 GHz) and J (12-16 GHz) natural rubber composites for antenna application were prepared and characterized. The main objective of this current research is to develop a flexible microwave shielding material to reduce electromagnetic inference (EMI) effect. Graphene nanoplatelet and cobalt nanowire was selected for improving electric and magnetic losses. The flexible rubber composite was prepared using two-roll mill process and cured at an tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The SE of reflection (SER) and absorption (SEA), and total SET mechanisms could be estimated as follows. [27] R ¼ S 11 j j 2 ¼ S 22 j j 2 , ð1Þ…”
Section: Characterizationsmentioning
confidence: 99%
“…The SE of reflection (SER) and absorption (SEA), and total SET mechanisms could be estimated as follows. [27] R ¼ S 11 j j 2 ¼ S 22 j j 2 , ð1Þ…”
Section: Characterizationsmentioning
confidence: 99%
“…Figure 4(B) exhibits the constitute and dimensions of sample holder. [25][26][27][28] Tables 3, 4, 5, and 6 display the attenuation loss dB at frequency range (E, F, I, and J band) in Un-modified and surface-modified epoxy HMR designations at different thickness "2, 2.5, and 3 mm." The SE of HMR composites improved with frequency and via high Ag/Ni content.…”
Section: Shielding Behaviormentioning
confidence: 99%
“…23 Magnetic nanofillers like cobalt and Fe 3 O 4 contribute toward EMI shielding by absorption of microwaves. [24][25][26][27][28] In our previous publications, 29 we have shown that GNRs can be a good option for EMI shielding with the requirement of very small weight % of the nanofiller. Sandwiched polymer multiwalled CNT (MWCNT) composites have also shown high EM attenuation capabilities.…”
Section: Introductionmentioning
confidence: 98%
“…When conjugated with ferromagnetic nanoparticles, these fillers are known to increase EM attenuation by manifolds 23 . Magnetic nanofillers like cobalt and Fe 3 O 4 contribute toward EMI shielding by absorption of microwaves 24–28 . In our previous publications, 29 we have shown that GNRs can be a good option for EMI shielding with the requirement of very small weight % of the nanofiller.…”
Section: Introductionmentioning
confidence: 99%